Evaluation of Ulcer Protective Activity of Morus alba L. Extract-Loaded Chitosan Microspheres in Ethanol-Induced Ulcer in Rat Model. (30th September 2022) - Garg, Sarita; Singla, Rajeev K.; Rahman, Md. Mominur; Sharma, Rohit; Mittal, Vineet
Abstract : Due to an unhealthy lifestyle, gastric ulcers have become a very common disease these days. Moreover, the side effects linked with the prolonged use of conventional treatments have shifted the paradigm towards herbal therapies. The leaves of Morus alba L. (Family-Moraceae) have been traditionally used for a large number of metabolic diseases. In the present research, we focused on the development of chitosan microspheres using extracts of leaves of Morus alba L. and their evaluation for gastroprotective efficacy against ethanol-induced ulcers in experimental rats. The process of development of M. alba extract microsphere (MEM) is also optimized using the Box-Behnken design. The formulation was prepared at optimized conditions (chitosan concentration (1.66% w/w), volume of glutaraldehyde (4.69 mL), and stirrer rotation per minute, RPM, 854.8), and the percentage yield ( Y 1 ) of the resulted microspheres is ∼95% with an encapsulation efficiency (EE) of ( Y 2(rutin) ) ∼86%, Y 2(quercetin) ) ∼85%, and particle size ( Y 3 ) of ∼40 µ m. The MEM prepared at optimized conditions can also be characterized for various parameters to ensure the uniformity of parameters. Also, the drug release studies indicated that the percentage release of rutin and quercetin from MEM was enhanced as compared to M. alba extract (ME) alone. Furthermore, in vivo analysis of the antiulcer potential of pretreatment with ME and MEM (500 mg/kg p.o.) in rats indicated that mucosal lesions, gastric juice volume, and total acidity were significantly altered as compared to ethanol-treated animals. Histopathology of tissue sections also confirmed the protection of gastric mucosa on pretreatment with MEM at 500 mg/kg p.o. On the basis of these findings, we can conclude that prepared microspheres can be used to develop a sustained release formulation of extract for the management of gastric ulcers. However, additional research is needed to establish the specific mechanisms of M. alba's antiulcer efficacy.